Dilated cardiomyopathy in 151 Irish Wolfhounds: Characteristic clinical findings, life expectancy and causes of death. (March 2019) - Vollmar, C.; Vollmar, A.; Keene, B.W.; Fox, P.R.; Reese, S.; Kohn, B.
Highlights: Irish Wolfhounds have a high prevalence of familial dilated cardiomyopathy. Other common disease predispositions adversely affect life expectancy in Irish Wolfhounds. In Irish Wolfhounds, decompensated dilated cardiomyopathy results in biventricular heart failure with pleural effusion. After development of congestive heart failure about 90% of deaths have a cardiac cause. Almost 50% of Irish Wolfhounds with preclinical dilated cardiomyopathy die from non-cardiac related causes. Abstract: Dilated cardiomyopathy (DCM) is an important cause of morbidity in Irish Wolfhounds (IW), a breed also predisposed to neoplastic and orthopedic diseases that shorten life expectancy. The objective of this study was to investigate survival and causes of death in IW with DCM and to characterise the clinical findings of DCM over time. Data from cardiovascular examinations performed in 1591 IW, including echocardiography and electrocardiography, were retrospectively evaluated. IW with DCM on medical therapy with long term longitudinal follow-up were included in this study ( n  = 151; 95 males, 56 females). Based on their clinical status at initial diagnosis, IW were classified into one of three groups: preclinical DCM with sinus rhythm (PC-DCM-SR, n  = 35), preclinical DCM with atrial fibrillation (PC-DCM-AF, n  = 87), and congestive heart failure with DCM and AF (CHF-DCM-AF, n  = 29). Survival data were analyzed using cumulative incidence functions, Kaplan–Meier and Cox regression. CHF was predominantly characterized by chylous pleural and mild pericardial effusions. Causes of death were cardiac (CD) in 73/151 and non-cardiac (non-CD) in 62/151; 16 dogs remained alive at study end. The majority of deaths in both preclinical DCM groups were non-CD (PC-DCM-AF = 51.9% non-CD, 48.1% CD; PC-DCM-SR, 65.5% non-CD, 34.5% CD). In the CHF-DCM-AF group most dogs (89.6%) experienced a CD. Median survival of the CHF-DCM-AF group (7.3 months) was significantly shorter than in the PC-DCM-AF group (21.9 months) or PC-DCM-SR group (29.1 months, P  = 0.001). CHF-DCM-AF in IW was associated with reduced life expectancy and CD, while most IW with preclinical DCM died from non-cardiac causes.